Exploring the Feasibility of Opportunistic Diabetic Retinopathy Screening with Handheld Fundus Cameras in Primary Care - Rêgo, Sílvia (2024)
Funding Information: This work was supported by EyeFundusScopeNEO: Demonstration of EyeFundusScope with Non-Expert Ophthalmology Users, cofounded by Portugal 2020, and framed under the Operational Program Competitiveness and Internationalization (COMPETE 2020) and European Regional Development Fund from the European Union, with operation code POCI-01-0247-FEDER-038400. The Funder had no role in the study design, implementation, and analysis. Publisher Copyright: © 2024 by the authors.